2019
DOI: 10.1136/jclinpath-2019-205732
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression on routine samples of non-small cell lung cancer: results and critical issues from a 1-year experience of a centralised laboratory

Abstract: AimsOur laboratory is a centralised centre receiving routine non-small cell lung cancer (NSCLC) samples for programmed death ligand-1 (PD-L1) immunohistochemical (IHC) evaluation. Since literature data are not concordant here we review our clinical records to assess the rate of PD-L1 positive and negative NSCLC cases in real-world practice.MethodsPD-L1 expression was evaluated by a validated 22C3 IHC labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
(12 reference statements)
2
30
0
Order By: Relevance
“…For example, our large referral center often receives direct smears for EGFR and BRAF DNA‐based mutational testing and material suspended in formalin for CB preparation and PD‐L1 testing from cytopathologists and/or clinicians working in peripheral institutions or hospitals. Indeed, we recently showed that, as opposed to surgical resections and histological biopsies, CBs outsourced from different institutions very frequently lack PD‐L1 expression and scarcely display high levels of PD‐L1 expression 22 . These observations clearly suggest that standardization of fixation time is critical for specimen preservation and reliable test results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, our large referral center often receives direct smears for EGFR and BRAF DNA‐based mutational testing and material suspended in formalin for CB preparation and PD‐L1 testing from cytopathologists and/or clinicians working in peripheral institutions or hospitals. Indeed, we recently showed that, as opposed to surgical resections and histological biopsies, CBs outsourced from different institutions very frequently lack PD‐L1 expression and scarcely display high levels of PD‐L1 expression 22 . These observations clearly suggest that standardization of fixation time is critical for specimen preservation and reliable test results.…”
Section: Discussionmentioning
confidence: 99%
“…PD‐L1 ICC was carried out with two different assays: (a) a validated laboratory developed test (LDT) based on concentrated DAKO 22C3 anti‐PDL1 primary antibody (Dako, Carpinteria, California) performed with Ventana's detection systems on the BenchMark XT platform (Ventana, Tucson, Arizona) 22 ; (b) the companion diagnostic kit SP263 assay (Ventana), following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 outbreak, the laboratory kept performing predictive molecular testing on tumour tissue specimens. [5][6][7][8] However, laboratory organisation needed to be completely reshaped to limit personnel number and working hours. Before the COVID-19 outbreak, our laboratory adopted, in most cases, laboratorydeveloped tests (LDTs).…”
Section: Introductionmentioning
confidence: 99%
“…T‐cell exhaustion due to binding of PD‐1 and PD‐L1 induces immune evasion of cancer cells from anti‐cancer immune responses . The percentage of PD‐L1‐positivity in cancer cells, named the tumor proportion score (TPS), is also considered a predictive biomarker for anti‐PD‐1/PD‐L1 therapy in lung cancer . Several monoclonal antibodies such as 22C3, 28‐8, SP263, and SP142 have been used for immunohistochemistry (IHC) to detect PD‐L1 expression, and clones 22C3 and SP142 are now available for companion and complementary diagnostics .…”
Section: Introductionmentioning
confidence: 99%